The Effects of Age, Memory Performance, and Callosal Integrity on the Neural Correlates of Successful Associative Encoding - de Chastelaine, Marianne (Oxford University Press, 2011)
This functional magnetic resonance imaging study investigated the relationship between the neural correlates of associative memory encoding, callosal integrity, and memory performance in older adults. Thirty-six older and 18 young subjects were scanned while making relational judgments on word pairs. Neural correlates of successful encoding (subsequent memory effects) were identified by contrasting the activity elicited by study pairs that were correctly identified as having been studied together with the activity elicited by pairs wrongly judged to have come from different study trials. Subsequent memory effects common to the 2 age groups were identified in several regions, including left inferior frontal gyrus and bilateral hippocampus. Negative effects (greater activity for forgotten than for remembered items) in default network regions in young subjects were reversed in the older group, and the amount of reversal correlated negatively with memory performance. Additionally, older subjects' subsequent memory effects in right frontal cortex correlated positively with anterior callosal integrity and negatively with memory performance. It is suggested that recruitment of right frontal cortex during verbal memory encoding may reflect the engagement of processes that compensate only partially for age-related neural degradation.